Use of mixed Li/K metal TMP amide (LiNK chemistry) for the synthesis of [2.2]metacyclophanes - Blangetti, Marco; Fleming, Patricia; O'Shea, Donal F. (Beilstein Journal of Organic Chemistry, 2011)
A new two-step general approach to [2.2]metacyclophane synthesis from substituted m-xylenes is described. The strategy employs a selective benzylic metalation and oxidative C–C bond formation for both synthetic operations. Regioselective benzylic metalation is achieved using the BuLi, KOt-Bu, TMP(H) (2,2,6,6-tetramethylpiperidine) combination (LiNK metalation conditions) and oxidative coupling with 1,2-dibromoethane. The synthetic ease of this approach compares favourably with previously reported methods and allows for ready access to potentially useful planar chiral derivatives.
Keywords: benzylic metalation; LiNK chemistry; [2.2]metacyclophane; oxidative coupling; planar chirality